Resilience Profile of Children with Special Needs and the Importance of Guidance and Counseling Services - Nurhayati, Novida; Habsy, Bakhrudin All; Budiyanto; Sartinah, Endang Pudjiastutik (Indonesian Academy of Social and Religious Research (IASRR), 2023)
Children with special needs are children who need special services to develop their potential in education, social services, guidance and counseling services, and various types of other special services. In reality, not many people understand or know children with special needs, so there is still much discrimination that occurs. This discrimination is not only from the community around them but also from their own families. This discrimination leads to a stressful situation, resulting in possible difficulties in participating in educational programs or other skills. Therefore, an important aspect that they need to adapt to difficult situations or stressful conditions is resilience. This research aims to describe and understand resilience in children with special needs. The method used in writing this article is the literature study method, where data is obtained by a series of activities related to library data collection methods, reading and recording, and processing research materials. The source of resilience formation itself comes from within and outside the individual internal factors that can affect children with special needs in bringing up resilience, which are emotion regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and reaching out. The implementation of counseling guidance services itself is almost the same as normal children in general according to their needs, which are described as follows: planning, implementation, and evaluation of guidance and counseling. Therefore, the important role of guidance and counseling services for children with special needs is needed.